Safety and activity of ibrutinib in combination with durvalumab in patients with relapsed or refractory follicular lymphoma or diffuse large B‐cell lymphoma. Issue 1 (6th November 2019) - Herrera, Alex F.; Goy, Andre; Mehta, Amitkumar; Ramchandren, Radhakrishnan; Pagel, John M.; Svoboda, Jakub; Guan, Shanhong; Hill, John S.; Kwei, Kevin; Liu, Emily A.; Phillips, Tycel
Abstract: This phase 1b/2, multicenter, open‐label study evaluated ibrutinib plus durvalumab in relapsed/refractory follicular lymphoma (FL) or diffuse large B‐cell lymphoma (DLBCL). Patients were treated with once‐daily ibrutinib 560 mg plus durvalumab 10 mg/kg every 2 weeks in 28‐day cycles in phase 1b without dose‐limiting toxicities, confirming the phase 2 dosing. Sixty‐one patients with FL (n = 27), germinal center B‐cell (GCB) DLBCL (n = 16), non‐GCB DLBCL (n = 16), and unspecified DLBCL (n = 2) were treated. Overall response rate (ORR) was 25% in all patients, 26% in patients with FL, 13% in patients with GCB DLBCL, and 38% in patients with non‐GCB DLBCL. Overall, median progression‐free survival was 4.6 months and median overall survival was 18.1 months; both were longer in patients with FL than in patients with DLBCL. The most frequent treatment‐emergent adverse events (AEs) in patients with FL and DLBCL, respectively, were diarrhea (16 [59%]; 16 [47%]), fatigue (12 [44%]; 16 [47%]), nausea (9 [33%]; 12 [35%]), peripheral edema (7 [26%]; 13 [38%]), decreased appetite (8 [30%]; 11 [32%]), neutropenia (6 [22%]; 11 [32%]), and vomiting (5 [19%]; 12 [35%]). Investigator‐defined immune‐related AEs were reported in 12/61 (20%) patients. Correlative analyses were conducted but did not identify any conclusive biomarkers of response. In FL, GCB DLBCL, and non‐GCB DLBCL, ibrutinib plus durvalumab demonstrated similar activity to single‐agent ibrutinib with the added toxicity of the PD‐L1 blockade; the combination resulted in a safety profile generally consistent with those known for each individual agent.